DILEMA UPAH BURUH DAN LAPANGAN KERJA BARU - Rahmawati, Rahmawati (STIA SATYA NEGARA PALEMBANG, 2023)
In discussing wages, not only employers and workers/ laborers have an interest, but the government, as well as the community in general also have an interest in this system. Entrepreneurs have an interest in managing their capital, how to manage their capital as well as possible by obtaining maximum results. Workers and their families are very dependent on the wages they receive to be able to meet their needs for clothing, food, housing and other needs. In the formulation of wages, workers/labourers and entrepreneurs have different tendencies. Workers/labourers have a tendency to get a lot of wages to achieve a good life. Employers have a tendency to provide low wages to workers because wages are seen as a reduction in profits. Facing this, the Government sometimes has to intervene through its policies, because the issue of wages will also affect the level of prosperity of the community and the state. In this case, the Government acts more as a mediator between the conflicting interests of employers and workers/labor. The government must be able to be fair in issuing its policies related to this wage issue